Pemberian ekstrak cassia surattensis pada mencit dalam mengendalikan infeksi cacing kremi (Aspiculuris tetraptera dan Syphacia obvelata): Administering cassia surattensis extract to mice in controlling (Aspiculuris tetraptera and Syphacia obvelata) pinworm infection - Sri Wahyuni; Sunarso Sunarso; Bambang Prasetiyono; Fadjar Satrija (Fakultas Peternakan Universitas Papua, 2023)
The anthelmintic activity of Cassia surattensis extract was strongest compared to C. siamea, C. fistula, and C. spectabilis extracts against Haemonchus contortus shown in previous studies. The study aimed to test the effectiveness of C. surattensis leaf extract against adult pinworms in mice (Mus musculus), based on the number eggs per gram feces (EPG) and the number of worm. A total of 30 male Deutschland Denken Yoken (ddY) strain mice aged 1.5-2 months with average body weight (bw) of 24.3 g were used in this study. The treatments applied included P0 = negative control, P1 = administration of C. surattensis extract at a dose of 125 mg/kg bw, P2 = administration of C. surattensis extract at a dose of 250 mg/kg bw, P3 = administration of C. surattensis extract at a dose of 500 mg/kg bw, and P4 = positive control. Administration of C. surattensis extracts for three consecutive days, according to the dose of each treatment. The efficacy of the extract of C. surattensis was evaluated by looking at the decrease in the number of EPG and the number of worms at the time of necropsy. The results showed that the maximum efficacy of the extract of C. surattensis at a dose of 500 mg/kg bw against pinworms with a decrease in EPG and the number of worms was 54.11 - 82.47% and 41,60%. This proves that C. surattensis extract has significant efficacy as an antinematode, so that it can be used as a conventional anthelmintic